Optimal scheduling of agricultural machines in hilly mountainous areas based on NSGA-Ⅱ-SA hybrid algorithm with applications - Liu, Huanyu; Luo, Jiahao; Zhang, Lihan; Wang, Fulin; Wang, Shuang (International Journal of Agricultural and Biological Engineering, 2025)
Optimizing the scheduling of farm machinery is essential to meet farmers’ requirements, minimize scheduling costs, and save time. This study focuses on scheduling farm machinery in multiple cooperatives across various regions, aiming to minimize scheduling costs and reduce scheduling time. Initially, a multi-constraint hybrid clustering algorithm is employed to assign farmland to each farm machinery cooperative by clustering before scheduling. Subsequently, an enhanced version of the Non-dominated Sorting Genetic Algorithm-Ⅱ (NSGA-Ⅱ) is proposed, integrating a local search strategy based on congestion-based neighborhood search and the Simulated Annealing (SA) algorithm to develop the NSGA-Ⅱ-SA algorithm. This hybrid multi-objective evolutionary algorithm effectively optimizes scheduling costs and time. The model’s validity and the algorithm’s superiority are demonstrated through a Web-based multi-region agricultural machine scheduling system and an example study. Experimental results show that the NSGA-Ⅱ-SA algorithm significantly reduces scheduling costs and time, as well as the number of scheduled farm machines, outperforming other algorithms with reductions of 9.8%, 3.1%, and 8.7% in total scheduling costs, and 12.5%, 13.4%, and 11.6% in total scheduling time. This research establishes a theoretical framework for multi-region agricultural machine scheduling in hilly and mountainous areas, enhancing agricultural production efficiency. Keywords: multi-region agricultural machine scheduling, hilly mountainous area, hybrid optimization algorithm, agricultural machine scheduling system DOI: 10.25165/j.ijabe.20251805.9106 Citation: Liu H Y, Luo J H, Zhang L H, Wang F L, Wang S. Optimal scheduling of agricultural machines in hilly mountainous areas based on NSGA-Ⅱ-SA hybrid algorithm with applications. Int J Agric & Biol Eng, 2025; 18(5): 234–245.